Pembiayaan Kredit Pemilikan Rumah (KPR) Subsidi Untuk Meningkatkan Kesejahteraan Masyarakat Berpenghasilan Rendah - Mansur Azis; Gista Neli Mariskha (Institut Agama Islam Negeri Ponorogo, 2023)
The house is a primary need not easily owned by everyone first for low-income people. This study aims to determine the implementation, inhibiting factors, and impact of mortgage loans. This research was conducted because there has been no similar research that includes information from housing developers. The context for improving the community's welfare has not yet been studied. This research is qualitative research based on field research. Data were obtained from interviews with customers, banks, and housing developers. The results show that despite the difficulties in collecting housing loan requirements, it can help and make it easier for people to own a house. There are inhibiting factors, including public awareness, problems with checking BI, dishonesty in the community about salaries, insufficient filing, difficulty obtaining salary certificates, non-strategic house locations, licensing regulations, and bank regulations during the pandemic. Meanwhile, the impact of home ownership loans on customers is to increase the customer's obligations or debts in installments every month. For housing developers, subsidized housing loans make developers take longer to find a location for housing construction that fits the government budget. On the other hand, developers also failed to realize sales due to the pandemic. Meanwhile, for the Karanganyar State Islamic Savings Bank, subsidized housing loans made the obligation to return funds to the government increased. It can be concluded that subsidized ownership credit can help and facilitate low-income people to own a house.